THE EFFECTIVENESS OF DIODE LASER 810 NM IN THE REMOVAL OF ORAL PYOGENIC GRANULOMA IN REPETITIVE PULSED MODE (Iraqi Journal of Medical Sciences, 2018)
Background: A variety of benign soft tissue swellings can be found arising from oral mucosa, most of which are inflammatory hyperplasia and granuloma. Surgical diode lasers have been used in oral surgical procedures with beneficial and undoubted operative advantages and a better quality of the outpatient operation compared with electro- and coldblade techniques. Objective: To assess the effectiveness of diode laser 810 nm in the removal of pyogenic granuloma of oral cavity in repetitive pulsed mode.Methods: This study was conducted at the consultation clinic of the Maxillofacial Surgery Department in the Al-Imamein Al-Kadhiemein Medical City on 35 patients who suffered from oral pyogenic granuloma. The period of the study was from January 2013 to January 2015. The laser used in this study was diode laser 810 nm in repetitive pulsed mode. The maximum power was 5-8 watts. The pulse duration was 0.2-0.4 second and 0.2-0.4 second pulse interval. Excisional biopsies were sent for Histopathological study. Clinical examination was done and had included presence of swelling, infection, disturbance of function, pain and bleeding.Results: Patients with pyogenic granuloma were treated efficiently with repetitive mode of diode laser 810 nm. Minimal to moderate swelling, no disturbance of function, no infection and mild pain were observed postoperatively, no bleeding was seen neither intraoperatively nor postoperatively.Conclusion: Repetitive pulsed mode of diode laser 810 nm is efficient and safe in removal of pyogenic granuloma of oral cavity.Keywords: Diode laser, oral pyogenic granulomaCitation: Al-Alawi AS. The effectiveness of Diode Laser 810 nm in the removal of oral pyogenic granuloma in repetitive pulsed mode. Iraqi JMS. 2017; Vol. 15(3): 262-267. doi: 10.22578/IJMS.15.3.7
Keywords: Diode laser; oral pyogenic granuloma